2021
DOI: 10.1053/j.gastro.2021.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Manifestations of Inflammatory Bowel Disease: Current Concepts, Treatment, and Implications for Disease Management

Abstract: Inflammatory bowel diseases (IBDs) are systemic diseases that manifest not only in the gut and gastrointestinal tract, but also in the extraintestinal organs in many patients. The quality of life for patients with IBD can be substantially affected by these extraintestinal manifestations (EIMs). It is important to have knowledge of the prevalence, pathophysiology, and clinical presentation of EIMs in order to adapt therapeutic options to cover all aspects of IBD. EIMs can occur in up to 24% of patients with IBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
228
1
26

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(361 citation statements)
references
References 133 publications
(176 reference statements)
7
228
1
26
Order By: Relevance
“…As the total number of patients was 508, of whom 51 had been diagnosed with sacroiliitis during their disease course, the prevalence of sacroiliitis was roughly 10% in our study group. This is lower, than we expected, as other studies reported greater prevalence [21][22][23][24][25]. Vertebral column involvement in the form of spondylitis or ankylosing spondylitis was seen in 25 patients total-18 females and 7 males.…”
Section: Extraintestinal Manifestations Affecting Different Organ Sys...contrasting
confidence: 56%
“…As the total number of patients was 508, of whom 51 had been diagnosed with sacroiliitis during their disease course, the prevalence of sacroiliitis was roughly 10% in our study group. This is lower, than we expected, as other studies reported greater prevalence [21][22][23][24][25]. Vertebral column involvement in the form of spondylitis or ankylosing spondylitis was seen in 25 patients total-18 females and 7 males.…”
Section: Extraintestinal Manifestations Affecting Different Organ Sys...contrasting
confidence: 56%
“…Although cellular sources of IL-33 are different in IBD and pancreatitis, IL-33 mediates tissue fibrosis in both disorders through induction of pro-fibrogenic factors such as IL-13. Moreover, pancreatitis sometimes develops as an extraintestinal manifestation of IBD ( Rogler et al, 2021 ). IL-33 might be one of pathogenic cytokines accounting for simultaneous occurrence of colitis and pancreatitis though further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…UC is an urgent global public health concern. Although conventional drugs such as 5-aminosalicylates, hormones, and immunosuppressive agents have played a good role in the treatment of UC, they still failed to achieve ideal effects and were often accompanied by side effects [ 5 ]. In China, CHM prescriptions have been widely used to treat UC and show beneficial preventive and therapeutic effects [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…UC is a dynamic disease with severity that can change over time [ 4 ], and the etiologies have not been fully elucidated. The therapeutic armamentarium for UC is expanding [ 1 ]; however, common therapies have been reported to be far less effective than ideal [ 5 ].…”
Section: Introductionmentioning
confidence: 99%